Dose-response assessment of chemically modified curcumin in experimental periodontitis - de Almeida Brandão, Dayane [UNESP]; Spolidorio, Luis Carlos [UNESP]; Johnson, Francis; Golub, Lorne M.; Guimarães-Stabili, Morgana Rodrigues [UNESP]; Rossa, Carlos [UNESP] (Wiley, 2019)
Background: CMC2.24, a novel tri-ketonic chemically modified compound based on natural di-ketonic curcumin, has been shown to reduce bone loss and inflammatory mediators in experimental periodontitis, however, a potential dose-response relationship was not determined. The purpose of this study was to assess the effects of different doses of CMC2.24 on inflammation and bone resorption in vivo and also to describe on the effects of CMC2.24 on macrophage response. Methods: CMC2.24 was administered daily to animals for 28 days by oral gavage, at the following doses: 0 (control), 1, 3, 10, and 30 mg/kg of body weight. Experimental periodontitis was induced by injections of lipopolysaccharide (LPS) into the gingival tissues. Outcomes assessed were bone resorption, detection of tartrate-resistant acid phosphatase, and determination of gene expression. In vitro, macrophages (RAW264.7) were treated with different concentrations of CMC2.24: 1, 3, 10, and 30 μM and then subjected to different activation stimuli. Gene expression, phagocytic activity, production of reactive oxygen species (ROS) and cytokine production were evaluated. Results: CMC2.24 inhibited bone resorption, osteoclastogenesis, and tumor necrosis factor (TNF)-α expression in vivo. These beneficial responses reached maximum levels at a dose of 1 mg/kg, i.e. no dose-dependent effect. In vitro, CMC2.24 reduced the production of TNF-α and interleukin-10, inhibited phagocytic activity and stimulated production of ROS. A dose-dependent effect was observed only for ROS production. Conclusion: Low doses of CMC2.24 (1 mg/kg/day) administered orally were sufficient to significantly inhibit alveolar bone resorption associated with the experimental periodontal disease; whereas in vitro macrophage inflammatory gene expression and phagocytosis were reduced, whereas production of ROS was stimulated.
Keywords: bone resorption; chemically modified curcumin/analogs and derivatives; dose-response relationship; inflammation; macrophages; periodontal disease